Confidential Memo - Miners' Federation of Great Britain, 15 July 1926
1926-07-15 "Confidential Memo - Miners' Federation of Great Britain, 15 July 1926" [g0526001.jpg], 15 July 1926, Miners' Federation of Great Britain The Return to Work